Analisis Efektivitas Digitalisasi Pajak Terhadap Kepatuhan Wajib Pajak: Sebelum dan Sesudah Implementasi - Putri Amelia Savitri; Anna Sumaryati; Juli Ratnawati; Hermawan Triono (Jurnal Pendidikan Indonesia, 2025)
Tolerance is the attitude of mutual respect and respect for differences in opinions, beliefs, cultures, religions, or habits of others, while maintaining good manners and not imposing their will. The ethics of tolerance mean that we are kind and respectful of others who are different from us. For example, if there is a friend who has a different religion or way of life, we do not insult or vilify him, but we still respect him and live in harmony together. This article aims to find out the views and attitudes of the public towards the implementation of Pancasila values, especially in terms of the ethics of tolerance in the midst of social life. Through the distribution of questionnaires, data was collected to analyze the extent to which the community understood and applied the value of tolerance as a tangible manifestation of practicing the precepts of Pancasila, especially the second and third precepts. The results of this study are expected to provide an overview of the social conditions of the community related to national values and become the basis for the development of policies or programs that encourage social harmony. All data obtained is guaranteed confidentiality and is used solely for academic purposes.